Art appreciation : the expression of etching in printmaking through Mohd Fawazzie Arshad’s Artwork / Noor A’yunni Muhamad, Azian Tahir and Noor Enfendi Desa - Muhamad, Noor A’yunni; Tahir, Azian; Desa, Noor Enfendi (Universiti Teknologi MARA, Perak, 2021)
In art world, Intaglio is one of the printmaking techniques that focuses on incising metal surfaces such as copper, steel or zinc plate. By using intaglio technique in producing printmaking artworks, that includes etching, drypoint or even mezzotint approach, the only thing that matters is the development of form through the understanding of lights and dark which leads to the exploration of value in art and design. On 14th September 2020, an artwork exhibition titled SI+SA was held at Galeri Shah Alam, with the aim of this exhibition is celebrating art from the different backgrounds of artistes during Covid-19 pandemic phenomenon. Mohd Fawazzie Arshad is one of the featuring artistes who participated in this exhibition and presented his remarkable intaglio artwork which emphasises the value of element and principle in arts. In this writing, the author was granted with the opportunity to conduct an interview with Mohd Fawazie Arshad to discuss the insight in his artworks and how does his artwork embark a different perspective in intaglio printmaking. This interview scrutinised on what are the elements that inspired the artist to produce his artwork and what are the references that artist has used in terms of developing idea and style in his artwork making. In this writing also, Mohd Fawazie Arshad will also explain the process of his artwork making based on his studio practises. It is important to understand the artist’s studio environment in order to explore the techniques and medium which has been practised by the artist in his artwork making. Findings from this research will produce a complete exclusive write up about Mohd Fawazie Arshad past and present artwork. It will enliven the art industry and academic writing especially in the field of Malaysian Printmaking art scene.